The Advancement of Civilization and the Factors Behind the Destruction of the People of ʿĀd - Shofwan , Muhammad Ali Daei; Satrio, Baihaqi Rio; Sudrajat, Fadel; Putri, Siti Yulia (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the story of the people of ʿĀd as presented in the Qur'an as both a historical and theological reflection on the rise and fall of a civilization. The people of ʿĀd, who lived after the time of the Prophet Noah (peace be upon him), were known for their physical strength and technological superiority. They built magnificent cities with astonishing architecture in the region of Al-Aḥqāf, which is now believed to be located between Yemen and Oman. However, they rejected the call of the Prophet Hūd to worship the one God and abandon their corrupt behavior. As a result of their defiance, God sent a punishment in the form of a prolonged drought and a devastating storm as a reprimand for their arrogance and moral transgressions.The aim of this research is to explore the spiritual, moral, and historical values in the story of ʿĀd and to reflect on the relevance of its divine messages for modern civilization. The main issues examined are how the Qur'an portrays the advancement of ʿĀd’s civilization and what key factors led to their downfall from theological, sociological, and moral perspectives.The method used is qualitative descriptive, employing a thematic tafsir (exegesis) approach and historical analysis. Primary sources include the Qur'an—particularly verses discussing the people of ʿĀd in Surahs Al-Fajr, Al-Ḥāqqah, and Al-Aḥqāf—supported by both classical and contemporary tafsir literature. The findings indicate that the people of ʿĀd were a powerful and advanced civilization, but their destruction stemmed from arrogance and rejection of divine teachings. Their story stands as an eternal warning about the dangers of pride and the importance of obedience to God, offering moral lessons that remain relevant to contemporary society.